Characterization of the Proinflammatory Cytokine Profile during Acute SARS-CoV-2 Infection in People with Human Immunodeficiency Virus - Anzurez, Alitzel; Runtuwene, Lucky; Dang, Thi Thu Thao; Nakayama-Hosoya, Kaori; Koga, Michiko; Yoshimura, Yukihiro; Sasaki, Hiroaki; Miyata, Nobuyuki; Miyazaki, Kazuhito; Takahashi, Yoshimasa; Suzuki, Tadaki; Yotsuyanagi, Hiroshi; et al. (Japanese Journal of Infectious Diseases, 2024)
Persistent inflammation during chronic human immunodeficiency virus (HIV) infection may affect the immune response against severe acute respiratory syndrome-coronavirus 2 (SARS- CoV-2) infection. Plasma levels of multiple proinflammatory cytokines during acute SARS-CoV-2 infection were measured in people with HIV (PWH) with effective combination antiretroviral therapy. There were no significant differences in any of the measured cytokines between severity levels of coronavirus disease 2019 (COVID-19) in PWH, while most were significantly higher in HIV-uninfected individuals with severe COVID-19, suggesting that excess cytokines release by hyperinflammatory responses do not occur in individuals with severe COVID-19 with HIV infection. The strong associations between the cytokines observed in HIV-uninfected individuals, particularly between IFN-α/TNF-α and other cytokines, were lost in PWH. The steady-state plasma levels of IP-10, ICAM-1, and CD62E were significantly higher in PWH, indicating that they were in an enhanced inflammatory state. The absence of several inter-cytokine correlations was observed in in vitro lipopolysaccharide stimulus-driven cytokine production in PWH. These data suggest that inflammatory responses during SARS-CoV-2 infection in PWH are distinct from those in HIV-uninfected individuals, partially because of the underlying inflammatory state and/or impairment of innate immune cells.